Pre-Service EFL Teachers’ Anxiety during Teaching Practicum at Senior High School: Causes and Solutions - Nelidya Nabila Putri Candra (Universitas Negeri Surabaya, 2025)
Introduction to the Schooling Field (PLP) is a mandatory practice for the Bachelor of Education Program that provides an introduction to the field related to schooling carried out outside of higher education. In this study, the researcher focuses on what anxiety pre-service EFL teachers experience during the teaching practicum at senior high school and what solutions they find to that anxiety. Qualitative research is employed in this study to gather data with detailed insight. This research is a case study involving English language education students in the class of 2020 who have undergone PLP (Introduction to the Schooling Field) and become pre-service EFL teachers at partner schools. The researcher examines the information gathered, which is gathering information from the participants on the open-ended, close-ended questionnaire and also through interviews. Examining the data on the anxiety that pre-service English teachers experience due to cognitive, affective, and also social-cultural aspects when they are teaching in a senior high school and the solutions to the anxiety that they experience during the teaching practicum. Future research on the anxiety of aspiring EFL teachers should focus on anxiety-reduction techniques by investigating various educational environments, cutting-edge technology solutions, successful mentorship models, and extensive support networks. This will improve pre-service teachers' well-being and professional development while making learning more efficient and exciting for their students.